2014
DOI: 10.1002/acp.3019
|View full text |Cite
|
Sign up to set email alerts
|

How Awareness of Possible Evidence Induces Forthcoming Counter‐Interrogation Strategies

Abstract: We propose that suspects' counter-interrogation strategies vary as a function of their perception of the interrogator's knowledge about the events in question. The present study investigates the verbal behavior of guilty and innocent suspects when they are aware that there may be incriminating evidence against them. Participants (N = 143) took part in either a simulated act of terrorism or a benign task. They were then interviewed about their activities. Participants were randomly assigned to receive no additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 28 publications
8
64
0
Order By: Relevance
“…In a recent study, Luke and his colleagues (in press) informed some of their suspects that the interviewer may have reviewed video surveillance recordings. This manipulation induced a large proportion of guilty suspects to become highly forthcoming.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study, Luke and his colleagues (in press) informed some of their suspects that the interviewer may have reviewed video surveillance recordings. This manipulation induced a large proportion of guilty suspects to become highly forthcoming.…”
Section: Discussionmentioning
confidence: 99%
“…the interviewer knew that the suspect had been in the room where the crime took place), but it did specify the source of the evidence (that is, surveillance recordings). The guilty suspect informed about the evidence in the study by Luke and his colleagues (in press) demonstrated a bimodal distribution of forthcomingness: Many suspects were highly withholding, many suspects were highly forthcoming, and few suspects were on the middle of the scale. In the present study, we found a different distribution, wherein guilty‐informed suspects demonstrated more variation in their forthcomingness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations